Using soil water sensors to improve irrigation management - Chávez, José L., author; Evett, Steven R., author (Colorado State University. Libraries, 2012)
Irrigation water management has to do with the appropriate application of water to soils, in terms of amounts, rates, and timing to satisfy crop water demands while protecting the soil and water resources from degradation. In this regard, sensors can be used to monitor the soil water status; and some can be used to calculate irrigation amounts and to decide when to optimally irrigate. This article consists of two parts: 1) presentation of different soil water sensor technologies, and 2) accuracy assessment of selected sensors. The selected sensors included the Acclima (ACC) time domain transmissometer (Acclima, Inc., Meridian, ID), the CS616 and CS655 water content reflectometers (Campbell Scientific, Inc., Logan, UT), the Hydra Probe (Stevens Water Monitoring Systems, Inc., Portland, OR), and the 5TE (Decagon Devices, Inc., Pullman, WA). Sensed soil water content values, in a sandy clay loam soil and a silty clay loam soil, were compared with corresponding values derived from gravimetric samples and TDR readings. Factory based calibrations performed well for the ACC and CS655, but not for the other sensors. The ACC and CS655 sensors were promising for irrigation management, although proper installation is important. Evaluations indicated that a linear calibration for the ACC and the CS616 sensors could improve the water content readings.
Proceedings of the 24th annual Central Plains irrigation conference
Presented at Proceedings of the 24th annual Central Plains irrigation conference held on February 21-22 in Colby, Kansas.